Hubungan keyakinan diri (self efficacy), stres kerja, dukungan keluarga, dan penempatan ruangan kerja dengan ketahanan mental (hardiness) - Syafni, Syafni; Bayhakki , Bayhakki; Lestari, Widia; Wahyuni, Sri; Amir, Yufitriana (Holistik Jurnal Kesehatan, 2025)
Background: Hardiness is an individual's ability to manage, overcome, reduce and survive stress or unpleasant conditions in life. Purpose: To determine the relationship between self-confidence, work stress, family support and workspace placement and hardiness (mental resilience) among nurses Method: Correlational quantitative research with total sampling technique, the number of nurse samples eligible for analysis was 676 respondents. The statistical analysis test used was bivariate analysis of chi-square test and multiple linear regression analysis. Results: There were 570 nurses (84.3%) in the moderate self-efficacy category, 472 (69.8%) nurses' hardiness was in the high category, 595 nurses' work stress (88.1%) was in the mild category, judging from the amount of family support 555 (82.1%) were in the high category and based on the highest work room placement in the inpatient room, 244 (36%) nurses. The results of the multiple linear regression test showed that the coefficient of determination R square was 0.159 or using independent variables was able to explain the hardiness of 15.9% of the model. The results of the work stress regression analysis output with a significant value of p<0.001, standardized coefficients Beta (b) 0.126 and family support results are significant p<0.001 with standardized coefficients Beta (b) 0.352. Conclusion: Work stress and family support influence nurses' hardiness and the most dominant variable influencing nurses' mental resilience (hardiness) is family support   Keywords: Family Support; Hardiness; Nurses; Self-Efficacy; Work Stress; Workspace Placement.   Pendahuluan: Hardiness adalah kemampuan individu dalam mengelola, mengatasi, mengurangi, dan bertahan dari stres atau kondisi yang tidak menyenangkan dalam hidup. Tujuan: Untuk mengetahui hubungan keyakinan diri (self efficacy), stres kerja, dukungan keluarga, dan penempatan ruangan kerja dengan hardiness (ketahanan mental) perawat. Metode: Penelitian kuantitatif korelasional dengan teknik pengambilan sampel total sampling, jumlah sampel perawat dengan respon rate layak dianalisa 676 responden. Uji analisis statistik yang digunakan adalah analisis bivariat uji chi-square dan analisis regresi linear berganda. Hasil: Terdapat 570 perawat (84.3%) berada pada kategori self efficacy sedang, hardiness perawat berada pada kategori tinggi 472 (69.8%), stres kerja perawat 595 (88.1%) berada kategori ringan, dilihat dari besarnya dukungan keluarga 555 (82.1%) berada pada kategori tinggi, dan penempatan ruangan kerja tertinggi pada ruangan rawat inap  244 (36%) perawat. Hasil uji regresi linear berganda didapatkan nilai koefisien determinasi R square adalah 0.159 atau menggunakan variabel independen mampu menjelaskan hardiness sebanyak 15.9% dari model. Output analisis regresi stres kerja dengan nilai signifikan p<0.001, standardized coefficients Beta (b) 0.126 dan dukungan keluarga hasil signifikan p<0.001 dengan standardized coefficients Beta (b) 0.352. Simpulan: Stres kerja dan dukungan keluarga memengaruhi hardiness perawat dan variabel yang paling dominan memengaruhi terhadap ketahanan mental (hardiness) perawat adalah dukungan keluarga.   Kata Kunci: Dukungan keluarga; Hardiness; Penempatan Ruangan; Perawat; Self efficacy; Stres Kerja.